2004
DOI: 10.2298/apt0435017d
|View full text |Cite
|
Sign up to set email alerts
|

Influence of maltodextrin dextrose equivalent value on rheological and dispersion properties of sunflower oil in water emulsions

Abstract: Effect of dextrose equivalent (DE) of maltodextrin present in continuous phase on flow along with dispersion properties of sunflower oil in water emulsions has been investigated. Both, rheological and disperse characteristics of the emulsions were greatly influenced by continuous phase viscosity and thus by the DE value of maltodextrin.. The smaller DE value the greater high shear viscosity and the smaller the droplet size. Irrespective of the amount and DE value of maltodextrin used was, all the emulsions sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…Similar to our investigations, Lefranc-Millot et al [ 7 ] also found that CD only has a minor impact on viscosity [ 7 ], supporting the fact that the increase was caused by the changes in the dry matter content. The sample with 8 g/100 g Malt exhibited the highest Kokini OSS of all mayonnaises, which was unexpected, since the viscosity of dextrins usually decreases with the increase of their dextrose equivalent value [ 60 , 61 , 62 ]. Additionally, CD is a much more branched molecule than Malt, which is known to foster an increase in viscosity.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to our investigations, Lefranc-Millot et al [ 7 ] also found that CD only has a minor impact on viscosity [ 7 ], supporting the fact that the increase was caused by the changes in the dry matter content. The sample with 8 g/100 g Malt exhibited the highest Kokini OSS of all mayonnaises, which was unexpected, since the viscosity of dextrins usually decreases with the increase of their dextrose equivalent value [ 60 , 61 , 62 ]. Additionally, CD is a much more branched molecule than Malt, which is known to foster an increase in viscosity.…”
Section: Resultsmentioning
confidence: 99%
“…BGNMP concentrated with 5% maltodextrin had the highest WAI and BGNMP concentrated with 15% had the lowest WAI. Many of maltodextrin attributes introduced as a hydrocolloid to already complex systems are directly related to the product's texture properties (e.g., creaminess, thickness, smoothness, spreadability, pourability, flowability, brittleness, and hardness) (Dokiḉ, Dokiḉ, Sovilj, & Katona, ).…”
Section: Resultsmentioning
confidence: 99%
“…The observed trend of decreasing WAI of BGNMP with increased maltodextrin concentration can be linked to the hardness and brittleness associated with maltodextrin, which can retard the water absorption capabilities. This occurs when the maltodextrin is introduced to an already complex system (Dokiḉ et al, ). Furthermore, water absorption involves the action of successful hydrogen bonding in a system between components (Sathe, ).…”
Section: Resultsmentioning
confidence: 99%
“…No obstante, el material de pared no debe aumentar excesivamente la viscosidad de la solución, dado que la muestra no podrá pasar por el aspersor del secador. Debido a que la maltodextrina es un oligómero de cadena corta (entre 3 y 20 unidades de glucosa), el cual puede disolverse fácilmente en agua a altas concentraciones sin aumentar la viscosidad de manera significativa, suele usarse en la mayoría de los procesos de encapsulación [11,12]. Adicionalmente, debido a la importancia del microencapsulamiento de los aceites esenciales, para este estudio se seleccionaron el aceite de oliva y el aceite de almendras dado su perfil lipídico.…”
Section: Introductionunclassified